Medical emergencies in dental practice - Péter Felkai; Péter Kivovics; Tamás Felkai (Hungarian Dental Association, 2020)
The number of the medical emergencies in the dental office presumably will increase due to the prolonged duration of the interventions, the increased utilization of anesthesia and the stress of fear. The following three things are needed in order to prevent such emergencies: preparedness of the staff, availability of the appropriate medicines and devices. Authors overview the prevalence (19% to 67%) and occurrence (2-20/year) of emergency situations in the office. The most frequent medical problem was the syncope (16,0-54% of all emergencies), the second frequent problem was the diabetes- related problems and the third one was the hypertensive attack/crisis and allergic reactions. All the authors of the surveyed literature emphasize the importance of the "emergency plan" and the drill of the crew. Authors suggest a list of medicines and devices as an essential tool for the treatment of the medical emergencies. This suggestion can be a good source for making the existing professional guideline more accurate. Moreover, the analysis of the international literature points out the most important issues of the emergency treatment in the dental office and it can make the education more effective and the dentist fit for face to with the unforeseen and suddenly occurred emergency situations.